Jughead the hunger. Volume three - Tieri, Frank (Archie Comic Publications, Inc., 2019)
When Jughead discovers that he is a werewolf, he feels guilt for all the murders he might have committed in Riverdale and still must find a way to escape Betty Cooper, werewolf hunter.